Pengembangan Lembar Kerja Siswa (LKS) Berbasis Higher Order Thinking Skill (HOTS) dalam Mata Pelajaran Akuntansi Kelas X di SMK - Maharani, Indrian; Nuraina, Elva; Astuti, Elly (Universitas Pendidikan Indonesia, 2021)
This study aims to develop Higher Order Thinking Skill (HOTS) based Student Worksheets (LKS) on the subject of the basics of financial accounting. This research was conducted in class X Accounting by referring to the 4D development model which is applied to the third stage, namely define, design, development. The instruments used in this study were the LKS validation sheet, student response questionnaires, and learning outcomes tests. The results of validation from experts, limited tests and field tests to respondents (students) show that the HOTS-based worksheets developed by researchers have met the criteria of validity, practicality and completeness. Thus it can be concluded that the HOTS-based worksheets developed by researchers can be used by teachers to carry out effective and efficient learning evaluations. The increase in KKM scores on the completeness criteria also indicates that the use of HOTS-based worksheets can improve student achievement.